Restoring the tumour suppressive function of p53 as a parallel strategy in melanoma therapy - Lu, M; Miller, P; Lu, X (Elsevier, 2014)
The tumour suppressor p53 is a master sensor of stress and it controls the expression of hundreds to thousands of genes with diverse biological functions including cell cycle arrest, apoptosis, and senescence. Consequently p53 is the most mutated gene found in human cancer and p53 mutation rate varies from 5% to 95%. Importantly p53 activity is often inactivated in tumours expressing structurally wild type p53. Thus one of the major challenges in cancer research is to restore the tumour suppressive function of p53. Intensive studies in the past decade have demonstrated that in addition to mutation, p53 activities are largely regulated by cellular factors that control the expression level and/or transcriptional activities of p53. MDM2, MDM4, p14ARF and the ASPP family of proteins are among the most studied regulators of p53. With increased understanding of the complexity of p53 regulation, various p53 reactivating approaches are being developed. This review will focus on the recent understanding of p53 inactivation in melanoma and the approaches to reactivate p53 in preclinical studies. Recent success in the therapeutic targeting of the BRAFV600E oncogenic protein was accompanied with subsequent relapse caused by acquired drug resistance. Restoration of the tumour suppressive function of p53 presents a parallel cancer therapeutic opportunity alongside BRAFV600E inhibition. Thus targeted therapy and concurrent reactivation of p53 may be a fertile ground to achieve synergistic killing of the 50% of cancer cells that express structurally wild type p53. © 2014 Federation of European Biochemical Societies. Published by Elsevier B.V. All rights reserved.